Data collection for risk assessments on animal health: review protocol 2021. Issue 1 (21st January 2022) - Dórea, Fernanda C.; Swanenburg, Manon; Horigan, Verity; Han, Seungeun; Young, Beth; de Freitas Costa, Eduardo; de Souza Santos, Mariana Avelino; Evans, Daniel; Royall, Elizabeth; Aznar, Inma; Dhollander, Sofie
Abstract: In 2014, EFSA received a mandate from the European Commission (EC) to assess the risk and consequences of introduction of new vector‐borne diseases (VBDs), and to determine if further measures were needed. To support the work, a comprehensive and systematic extraction of data from the literature was conducted, covering 36 VBDs in 18 host mammalian species. Regular updates of this corpus of scientific evidence are needed to support risk assessments. The foundation set by the previous rounds of literature review for VBDs can be reused to provide efficient and reliable collection of scientific evidence to support EFSA needs in various areas of knowledge. EFSA has been requested to provide support to the EC via scientific opinions that would form the basis for the production of amending and implementing acts supporting Regulation 2016/429 (of the European Parliament and of the Council of 9 March 2016 on transmissible animal diseases and amending and repealing certain acts in the area of animal health – the "Animal Health Law"), which lays down rules for the prevention and control of animal diseases which are transmissible to animals or to humans. To support EFSA in keeping the available VBD knowledge as an up‐to‐date source of information for risk assessors, and in providing scientific opinions in matters related to Regulation 2016/429, the methodology for literature review has been further consolidated in seven specific areas of knowledge: experimental infections, pathogen survival, diagnostic tests performance, vaccines, preventive and curative treatments, vector treatments and geographical distribution. This document details the review protocol to update the available knowledge about the 36 VBDs within those seven areas since the last systematic literature reviews were carried out in 2017; as well as extend them to the terrestrial animals category A diseases in the "Animal Health Law".